Differences in Blood Pressure in Infants After General Anesthesia Compared to Awake Regional Anesthesia (GAS Study—A Prospective Randomized Trial). (September 2017) - McCann, M. E.; Withington, D. E.; Arnup, S. J.; Davidson, A. J.; Disma, N.; Frawley, G.; Morton, N. S.; Bell, G.; Hunt, R. W.; Bellinger, D. C.; Polaner, D. M.; Leo, A.; et al.
Abstract : BACKGROUND: The General Anesthesia compared to Spinal anesthesia (GAS) study is a prospective randomized, controlled, multisite, trial designed to assess the influence of general anesthesia (GA) on neurodevelopment at 5 years of age. A secondary aim obtained from the blood pressure data of the GAS trial is to compare rates of intraoperative hypotension after anesthesia and to identify risk factors for intraoperative hypotension. METHODS: A total of 722 infants ⩽60 weeks postmenstrual age undergoing inguinal herniorrhaphy were randomized to either bupivacaine regional anesthesia (RA) or sevoflurane GA. Exclusion criteria included risk factors for adverse neurodevelopmental outcome and infants born at <26 weeks of gestation. Moderate hypotension was defined as mean arterial pressure measurement of <35 mm Hg. Any hypotension was defined as mean arterial pressure of <45 mm Hg. Epochs were defined as 5-minute measurement periods. The primary outcome was any measured hypotension <35 mm Hg from start of anesthesia to leaving the operating room. This analysis is reported primarily as intention to treat (ITT) and secondarily as per protocol. RESULTS: The relative risk of GA compared with RA predicting any measured hypotension of <35 mm Hg from the start of anesthesia to leaving the operating room was 2.8 (confidence interval [CI], 2.0–4.1; P < .001) by ITT analysis and 4.5 (CI, 2.7–7.4, P < .001) as per protocol analysis. In the GA group, 87% and 49%, and in the RA group, 41% and 16%, exhibited any or moderate hypotension by ITT, respectively. In multivariable modeling, group assignment (GA versus RA), weight at the time of surgery, and minimal intraoperative temperature were risk factors for hypotension. Interventions for hypotension occurred more commonly in the GA group compared with the RA group (relative risk, 2.8, 95% CI, 1.7–4.4 by ITT). CONCLUSIONS: RA reduces the incidence of hypotension and the chance of intervention to treat it compared with sevoflurane anesthesia in young infants undergoing inguinal hernia repair. Abstract : Published ahead of print May 4, 2017.